Analysis of a study of the users, uses, and future agenda of the UMLS - Chen, Yan; Perl, Yehoshua; Geller, James; Cimino, James J (Journal of the American Medical Informatics Association : JAMIA, 2007)
The UMLS constitutes the largest existing collection of medical terms. However, little has been published about the users and uses of the UMLS. This study sheds light on these issues. We designed a questionnaire consisting of 26 questions and distributed it to the UMLS user mailing list. Participants were assured complete confidentiality of their replies. To further encourage list members to respond, we promised to provide them with early results prior to publication. Sector analysis of the responses, according to employment organizations is used to obtain insights into some responses. We received 70 responses. The study confirms two intended uses of the UMLS: access to source terminologies (75%), and mapping among them (44%). However, most access is just to a few sources, led by SNOMED, MeSH, and ICD. Out of 119 reported purposes of use, terminology research (37), information retrieval (19), and terminology translation (14) lead. Four important observations are that the UMLS is widely used as a terminology (77%), even though it was not designed as one; many users (73%) want the NLM to mark concepts with multiple parents in an indented hierarchy and to derive a terminology from the UMLS (73%). Finally, auditing the UMLS is a top budget priority (35%) for users. The study reports many uses of the UMLS in a variety of subjects from terminology research to decision support and phenotyping. The study confirms that the UMLS is used to access its source terminologies and to map among them. Two primary concerns of the existing user base are auditing the UMLS and the design of a UMLS-based derived terminology.